2016
DOI: 10.3389/fphys.2016.00487
|View full text |Cite
|
Sign up to set email alerts
|

Endurance Training Intensity Does Not Mediate Interference to Maximal Lower-Body Strength Gain during Short-Term Concurrent Training

Abstract: We determined the effect of concurrent training incorporating either high-intensity interval training (HIT) or moderate-intensity continuous training (MICT) on maximal strength, counter-movement jump (CMJ) performance, and body composition adaptations, compared with single-mode resistance training (RT). Twenty-three recreationally-active males (mean ± SD: age, 29.6 ± 5.5 y; trueV˙O2peak, 44 ± 11 mL kg−1·min−1) underwent 8 weeks (3 sessions·wk−1) of either: (1) HIT combined with RT (HIT+RT group, n = 8), (2) wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
98
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(106 citation statements)
references
References 52 publications
6
98
1
1
Order By: Relevance
“…Expired gases were sampled every 15 s using automated gas analysers (Moxus Modular VO 2 System, AEI Technologies, Pittsburgh, PA, USA) and peak oxygen uptake (VO 2peak ) was determined based on the two highest consecutive 15 s values achieved during the test (Fyfe et al 2016). Gas analyzers were calibrated prior to each test using known gas concentrations (21.0% O 2 and 0.03% CO 2 , 16.0% O 2 and 4.0% CO 2 ).…”
Section: Graded Exercise Test (Gxt) and Blood Samplingmentioning
confidence: 99%
“…Expired gases were sampled every 15 s using automated gas analysers (Moxus Modular VO 2 System, AEI Technologies, Pittsburgh, PA, USA) and peak oxygen uptake (VO 2peak ) was determined based on the two highest consecutive 15 s values achieved during the test (Fyfe et al 2016). Gas analyzers were calibrated prior to each test using known gas concentrations (21.0% O 2 and 0.03% CO 2 , 16.0% O 2 and 4.0% CO 2 ).…”
Section: Graded Exercise Test (Gxt) and Blood Samplingmentioning
confidence: 99%
“…Foreign related research also confirmed that combined with aerobic ability training of football player special athletic performance has many positive effects [6][7][8][9][10].Get oxygen transport capacity of athletes, the ability to pump the blood of the heart, vo2 Max, running from the game, the sprint frequency and number of the ball has been improved obviously.And thus put forward the judgment of maximum heart rate field test method [11], for the coaches to effectively control training provides a good guidance.…”
Section: Introductionmentioning
confidence: 89%
“…In studies that used interval training, five used the combination of the HIIT protocol with strength training 21,[23][24][25]28 , while four adopted the SIT principles for combined training 20,22,26,27 . Regarding the methodological quality of studies, one was classified as with low methodological quality 20 , six with medium quality 21,23,24,[26][27][28] and two with high quality 22,25 . Among the interventions used in the comparison with the combined protocol (HIIT / SIT) + RT, three studies adopted HIIT / SIT 22,27,28 seven RT 20,21,23,24,[26][27][28] and two CT + RT 24,25 .…”
Section: Resultsmentioning
confidence: 99%
“…Among the selected studies, four performed interventions in samples with eutrophic nutritional status [20][21][22][23] and five in overweight populations [24][25][26][27][28] [20][21][22][23][24][25][26] and seven cardiorespiratory fitness, specifically VO 2max in kg / ml / min. 20,22,[24][25][26][27][28] . In studies that used interval training, five used the combination of the HIIT protocol with strength training 21,[23][24][25]28 , while four adopted the SIT principles for combined training 20,22,26,27 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation